2006
DOI: 10.1128/jvi.00896-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Protective Lassa Virus Epitopes That Are Restricted by HLA-A2

Abstract: Recovery from Lassa virus (LASV) infection usually precedes the appearance of neutralizing antibodies, indicating that cellular immunity plays a primary role in viral clearance. To date, the role of LASV-specific CD8 ؉ T cells has not been evaluated in humans. To facilitate such studies, we utilized a predictive algorithm to identify candidate HLA-A2 supertype epitopes from the LASV nucleoprotein and glycoprotein precursor (GPC) genes. We identified three peptides (GPC 42-50 , GLVGLVTFL; GPC 60-68 , SLYKGVYEL;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 43 publications
1
72
0
2
Order By: Relevance
“…That binding beyond a certain threshold often does not correlate strongly with immunodominance, in both class I and class II contexts, has been pointed out in several studies (17,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47).…”
Section: Cd8mentioning
confidence: 99%
“…That binding beyond a certain threshold often does not correlate strongly with immunodominance, in both class I and class II contexts, has been pointed out in several studies (17,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47).…”
Section: Cd8mentioning
confidence: 99%
“…Likewise, the studies conducted by Botten et al demonstrated that infection of human HLA-A*0201-positive target cells with an rVACV could be used to detect naturally processed LASV-and LCMV-derived CD8 ϩ T cell epitopes (13,14).…”
Section: Identification Of Arenavirus-specific Cd8 ؉ T Cell-mediated mentioning
confidence: 99%
“…ϩ and CD4 ϩ T cell responses have clearly been associated with reduced pathology and protection against Old World arenaviruses in animal models of infection (13,14,50,56,99,101). Previous studies demonstrated that mice lacking CD8 ϩ T cells or the cytolytic protein perforin are incapable of resolving a primary LCMV infection (49,101).…”
Section: Cd8mentioning
confidence: 99%
See 2 more Smart Citations